2010
DOI: 10.3928/01477447-20100329-04
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Postoperative Acromial and Scapular Spine Fractures on the Results of Reverse Shoulder Arthroplasty

Abstract: Fractures of the acromion or scapular spine are recognized complications of reverse arthroplasty. This study reviewed the outcome of reverse arthroplasties with such fractures and compared the results to arthroplasties without the fractures. A consecutive series of 125 reverse arthroplasties were reviewed for the development of a postoperative acromial or scapular spine fracture. Nine cases were identified, all treated nonoperatively. Five fractures occurred from falls, and the remainder were fatigue fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 12 publications
1
80
1
3
Order By: Relevance
“…Despite deltoid induced acromial tilt in most patients, postoperative range of motion, Constant scores and subjective results were not diminished. In contrast, postoperative spine fractures (4 patients or 0.8% in this study), generally have poor results [65,66]. They often occur in the first year, and results of attempted internal fixation have been unsatisfactory.…”
Section: Acromial Insufficiencymentioning
confidence: 65%
“…Despite deltoid induced acromial tilt in most patients, postoperative range of motion, Constant scores and subjective results were not diminished. In contrast, postoperative spine fractures (4 patients or 0.8% in this study), generally have poor results [65,66]. They often occur in the first year, and results of attempted internal fixation have been unsatisfactory.…”
Section: Acromial Insufficiencymentioning
confidence: 65%
“…Often considered to be insufficiency stress fractures, 14 many of these fractures develop after various degrees of trauma. 4,9 Fractures occur along several different areas of the acromion; however, those that are sustained at the acromion attachment to the scapular spine (acromion base) have been associated with the worst prognosis. 9 The position of the baseplate screws may also contribute to the development of acromion fractures.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 Fractures occur along several different areas of the acromion; however, those that are sustained at the acromion attachment to the scapular spine (acromion base) have been associated with the worst prognosis. 9 The position of the baseplate screws may also contribute to the development of acromion fractures. Screws that are placed in the posterior-superior quadrant of the glenoid are typically directed toward the base of the acromion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All acromial fractures were treated with conservative management and resulted in limitation in function. Hattrup et al [40] reported improved functional outcome results with conservative management of acromial and scapular spine fractures with greater of 1 year of follow-up. The authors cautioned against open reduction and internal fixation due to the challenges of stable internal fixation around this particular location.…”
Section: Scapular Notchingmentioning
confidence: 99%